Comunicações Livres - Silva, Bruno Duarte Guimarães; Duarte, Denise Aparecida Sousa; Malacco, Felipe Silveira de Oliveira; Andrade, Paulo Renato Silva de; França, Alexsandra Pimentel; Morais, Bruno Vinícius Leite de; Baião, Fábio Eduardo de Araújo; Pinto, Gislaine Gonçalves Dias; Parreira, Luiza Rabelo; Nascimento, Maíra Máximo; Gorga, Pamela Emilse Naumann; Soares, Raquel Marques; et al. (Temporalidades, 2016)
Volume único.